Measurement of Service Quality in the Tiktok Shop Application Using the Method E-Servqual And IPA (Importance Performance Analysis): Pengukuran Kualitas Layanan Pada Aplikasi Tiktok Shop Menggunakan Metode E-Servqual Dan IPA (Importance Performance Analysis) - Sari, Putri Febriana; Suyatno, Dwi Fatrianto (Universitas Negeri Surabaya, 2023)
TikTokShop is an application that operates in the field of digital buying and selling transactions, with the aim of facilitating users in making transactions. The purpose of this research is to measure the quality of user service provided by TikTokShop to provide appropriate recommendations to improve service features and others. The method used is E-Servqual,which consists of dimensions such as efficiency, fulfillment, reliability, privacy, responsiveness, compensation and contact. Analysis was then carried out using the method E-Service Quality and Importance Performance Analysis to measure how users perceive the quality of TikTok's serviceShop. The population for this study includes all TikTok users who have made transactions on TikTokShop. The results of this study indicate an overall gap between users' perceptions of performance and their expectations, with a score of -0.36; indicates that the services provided by TikTokShop do not meet user expectations. After conducting an IPA analysis of the 27 indicators mapped on the Cartesian diagram with quadrants A, B, C, and D, there are 5 priority indicators for service improvement which are included in quadrant A.